FARM-VSS: A web-based visualizer and summarizer suite with Gen-AI-enabled interpretation for Fuzzy association rule mining - Vartul Shrivastava; Shekhar Shukla (SoftwareX)
In the current landscape of data analytics, Fuzzy Association Rule Mining (FARM) is being extensively employed to produce interpretable fuzzy rules. In the literature, various toolkits exist that assist practitioners in performing FARM-based inference on their dataset, but a comprehensive open-source GUI-enabled toolkit that facilitates Generative AI-based inference, customizable fuzzy partitioning and brute-force FARM Rules Explorer is scarce in existing toolkits. This research aims to bridge this gap by offering a comprehensive technical suite for FARM and Weighted FARM (WFARM) using the Fuzzy Apriori algorithm to aid researchers and practitioners.